The health‐related quality of life changes following surgery in patients with colorectal cancer: a longitudinal study. Issue 6 (18th March 2022) - Tang, Howard; Besson, Alex; Deftereos, Irene; Mahon, Bede; Cho, Jin; Faragher, Ian; Gough, Karla; Yeung, Justin
Abstract: Background: Colorectal cancer (CRC) is commonly treated with surgery and its success is frequently defined by cure rates. Impact on other aspects of health and wellbeing are less frequently considered in clinical practice. Patient‐reported outcome measures (PROMs) provide a useful means of assessing such impacts. This study examines changes in health‐related quality of life (HRQoL) after surgical resection using PROMs. Methods: A prospective, longitudinal study was undertaken in 49 adults receiving curative surgery for CRC. Participants completed the Functional Assessment of Cancer Therapy‐Colorectal (FACT‐C) before surgery, and at 2 to 4 weeks, 3 and 6 months post‐surgery. Linear mixed models were used to analyse FACT‐C wellbeing and subscale scores. Results: Patients reported a clinically important deterioration in functional and physical wellbeing 2 to 4 weeks post‐surgery (both P < 0.05); differences at 6 months after surgery were trivial. Conversely, patients reported clinically important improvement in emotional wellbeing at 2 to 4 weeks post‐surgery; this improvement was sustained at 3 and 6 months post‐surgery (all P < 0.05). For social wellbeing and colorectal cancer‐specific concerns, changes from before surgery at follow‐up assessments were not statistically significant (all P > 0.05). Conclusion: While physical aspects of HRQoL are affected in the short term by CRC surgery, clinically significant improvement in emotional wellbeing are reported early (2 to 4 weeks post‐surgery). Future research may help identify patients who are at greater risk of surgical impacts on health and wellbeing. Abstract : Patient‐reported outcome measures have been used to measure health‐related quality of life in surgical oncology. While physical aspects are affected in the short term by colorectal cancer surgery, clinically significant improvement in emotional wellbeing are reported early (2 to 4 weeks post‐surgery).